Resection of thumb metacarpal Ewings Sarcoma and primary reconstruction with a non-vascularized, autologous, osteoarticular metatarsal graft - Sharifudin, Mohd Ariff; Wan, Zulmi; Wan Ismail, Wan Faisham Numan; Mat Zin, Nor Azman (2014)
Introduction: Ewings sarcoma is a rare, malignant neoplasm; rarely originates in the bones of the hand. Historically, treatment involves a combination of chemotherapy and radiotherapy. The role of surgical intervention remains limited, depending on the anatomic location. Resection and reconstruction will usually result in reduced or loss of function. Methodology: We reviewed a case of an 11-year girl with Ewings sarcoma of the first metacarpal bone of her dominant right hand with a solitary lung metastasis. Results: Treatment consisted of neo- and adjuvant chemotherapy, and wide resection of the first metacarpal followed by reconstruction of her thumb with a non-vascularised, intercalated, autologous second metatarsal graft. The capsule of the graft’s metatarso-phalangeal joint was repaired to achieve mobility of the joint. Her donor site was reconstructed with an autologous tricortical iliac bone graft. Two years following surgery, she achieved near normal functioning of her dominant hand, with no donor site morbidity and local recurrence. The surgical techniques are described together with the excellent functional outcomes in the patient. Conclusion: The use of non-vascularised, autologous metatarsal bone graft to reconstruct the thumb following tumour resection is an excellent option available. It is relatively simple and can be performed as a single resection and reconstruction procedure.